Empowerment of social norms on water consumption - Pauline Pedehour; Lionel Richefort (Fondazione Eni Enrico Mattei (FEEM), 2021)
This study develops a model of water extraction with endogenous social norms. Many users are connected by a unique shared resource that can become scarce in case of over-exploitation. Preferences of individuals are guided by their extraction values and their taste for conformity to social norms which provide incentives to follow others. As the main result of this study, the uniqueness of the Nash equilibrium is established under a sufficient condition. Afterward, some comparative statics analysis shows the effects of change in individual heterogeneous parameters, conformism, and density of the network on the global quantity extracted. Welfare and social optimum properties are established to avoid the tragedy of the commons and sub-optimal consumptions of water. Lastly, this theoretical framework is completed by extensions to highlight levers of water preservation, including the calibration of social norm incentives.
Keywords: D04; D80; Q01; Q25; 330; Comparative statics; Conformism; Nash equilibrium; Network; Social norms; Water extraction